Efficacy of oral ketamine compared to midazolam for sedation of children undergoing laceration repair: A double-blind, randomized, controlled trial. Issue 26 (June 2016) - Rubinstein, Orit; Barkan, Shiri; Breitbart, Rachelle; Berkovitch, Sofia; Toledano, Michal; Weiser, Giora; Karadi, Natali; Nassi, Anat; Kozer, Eran
Abstract : Abstract: Objective: To assess the efficacy of oral ketamine versus oral midazolam for sedation during laceration repair at a pediatric emergency department. Methods: Children between 1 and 10 years requiring laceration repair were randomly assigned to 2 groups, treated either with oral midazolam (0.7 mg/kg) or with oral ketamine (5 mg/kg). Main outcomes measured were level of pain during local anesthesia, as assessed by the parent on a 10-cm visual analog scale (VAS) and the number of children who required intravenous sedation. Secondary outcomes included VAS by physician, pain assessment by child, maximal sedation depth assessed by the University of Michigan Sedation Scale, time until University of Michigan Sedation Scale 2 or more, general satisfaction of a parent and treating physician, length of procedure, total sedation time, and the incidence of any adverse events. Results: Sixty-eight children were recruited of which 33 were girls. Average age was 5.08 ± 2.14 years. Thirty-seven children were treated with ketamine and 31 with midazolam. Parent-assessed VAS in ketamine treated patients was 5.07 ± 0.75 compared with 3.68 ± 0.7 in midazolam treated patients [mean difference = 1.39 95% confidence interval (CI) –0.47 to 3.26]. Twelve (32%) of the children treated with ketamine required the addition of IV sedation compared to only 2 children (6%) of the children treated with midazolam [odds ratio (adjusted for age and gender) 6.1, 95% CI: 1.2 to 30.5]. The rest of the measured variables were similar between the groups, with no statistical significance. Discussion: No difference in the level of pain was found between ketamine and midazolam treated patients. Compared with oral midazolam (0.7 mg/kg), oral ketamine (5 mg/kg) was associated with higher rates of sedation failure, and thus is not recommended as a single agent for oral sedation in children requiring laceration repair.